FAKTOR YANG MEMPENGARUHI PEMILIHAN IUD PASCA PLASENTA PADA WUS DI PUSKESMAS WILAYAH KOTA MATARAM - Kisid, Kristiani (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2021)
The use of the Kb method is expressed by the Contraceptive Prevalence Rate (CPR). Based on Riskesdas (2013), the proportion of family planning use in risk groups, namely the group of married women aged 15-19 years, is 46%, this figure is still lower than the 2014 RPJM target of 60.1%. Younger married women use more modern short-term contraceptives such as injections and birth control pills, while older women use more long-term contraceptives such as IUD and sterile (BKKBN et al., 2012). The purpose of this study was to determine the description of the user profile and what factors influence the selection of post-placental IUDs in fertile aged women in the PKM, Mataram City area. This research is a descriptive analytic study. With a case control research design which is an analytic survey (survey) that concerns how risk factors are studied using a retrospective approach. The sample in this study was 40 respondents who were divided into 2 groups, namely 20 respondents for the user group and 20 respondents for the control group. The user profile of the respondents in this study is the post-placenta IUD which is most widely used in respondents with the age group of 20 - 35 years, namely a number of 19 respondents (95%). Most of them came from high school education level with a number of 15 respondents (75%). Most of them came from unemployed mothers / housewives, namely 17 respondents (85%). With the highest number of parity is multiparous, namely 12 respondents (60%). And all respondents 20 respondents (100%) have the goal of family planning is to delay pregnancy. There is a significant relationship between perceptions and attitudes with the use of the Post Placenta IUD in women in the working area of ??Puskesmas in Mataram City